Exercise induced operant conditioning of the H-reflex in stroke patients: Hopes for improving motor function through inducing plastic changes in the spinal pathways - Behdad Tahayori; David Koceja (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2019)
Background: Cerebrovascular accident is a major cause of disability. Stroke survivors suffer from various severity levels of movement impairment which would substantially affect their quality of life. Several methods have been investigated for improving movement in these patients. Most of the treatment approaches are geared toward inducing neuroplasticity in the brain. Here, we introduce a novel method to induce neuroplasticity in spinal cord to compensate the cerebral insult.  Purpose: The aim of this study was to examine the ability of hemiplegic stroke patients to volitionally down-regulate the soleus H-reflex and its functional consequence. A humancomputer interface was developed to monitor several neural and behavioral factors while subjects stood on a balance board. The interface would elicit an H-reflex when the criteria were met and would provide feedback to the patients about the amplitude of the H-reflex. Subjects were encouraged to down-regulate the amplitude of the reflex.  Results: The protocol was tested in 3 hemiplegic subjects. Subjects demonstrated the ability to down-regulate the H-reflex. The rate of success in this down-regulation was on average %80.1±9.96. This success rate was in strong agreement with improvement in gait symmetry and gait velocity.  Major findings: This study demonstrated that stroke survivors have the ability to down-regulate their spinal reflexes and this down-regulation was correlated with movement improvement. Conclusion. The results suggest that stroke patients have the ability to down-regulate the Hreflex amid corticospinal damages. This was accompanied by improvement in motor function.  Potential implications: The current study has provided proof of evidence to show that inducing plastic changes in the spinal cord can improve motor output in stroke survivors. This method could be another treatment approach for stroke impairment.